Marienlexikon herausgegeben im Auftrag des Institutum Marianum Regensburg von Prof. R. Baeumer und Prof. L. Scheffczyk, Bd. 1-6, St Otilien 1988-1994, Eos Verlag, ss. 672+704+718+ 722+704+872 - Gładyszewski, Ludwik (Vox Patrum, 1997)
review